The Thrombostat 4000 A Sensitive Screening Test for von Willebrand's Disease - Weippert-Kretschmer, Monika; Witte, Michaele; Budde, Ulrich; Vigh, Thomas; Volker, Kretschmer; Scharrer, Inge (Seminars in Thrombosis and Hemostasis, 1995)
The determination of the bleeding time (BT) is an essential diagnostic tool for von WilIebrand's disease (vWD). However, the standardized Simplate ® BT still displays many variables and disadvantages. The present study reports on the sensitivity of the in vitro bleeding test (IVBT) in 51 vWD cases of different types and severity in comparison to the Simplate BT, and the correlation of both to each other as well as to von Willebrand factor (vWF:RCo) activity. The IVBT was performed in two modifications (2 mmoIIL CaCl2 and 4 mmollL ADP) on the Thrombostat 4000.The IVBT, particularly with CaCl2, showed clearly higher sensitivity than the BT (CaCl2 : 84.3%, ADP: 61.7%, CaCl2 + ADP: 86.3, BT: 52.9%). The BT even failed in one patient with severe (type 2B) and in three with moderate vWD. The IVBT only failed in very mild forms of the disease (vWF: RCo > 25%). In addition, the IVBT with ADP showed a close correlation to the vWF:RCo activity (r2 = 0.73). The significantly lower correlation of the BT with vWF:RCo (r2 = 0.49) was particularly due to the poor results in vWD of type 2 (type 2:r2 = 0.29; types 1 and 3:r2 = 0.61). Finally, BT and IVBT-ADP correlated with each other (r2 = 0.53), a rather good correlation considering that both are complex functional tests. It can be concluded from our study that the IVBT not only may replace the BT for most applications, but is clearly superior to BT for the screening (IVBT-CaCl2) and control of therapy in vWD.
Keywords: von Willebrand's disease; bleeding time; ristocetin cofactor; Thrombostat 4000; therapy; von Willebrand's disease